Self-healing through visual and verbal art therapy - Simon, R. M. (Rita M.), 1921- (Jessica Kingsley Publishers, 2005)
Self-Healing Through Visual and Verbal Art Therapy explores the therapeutic properties of visual and verbal creativity and its capacity to act as a natural means of self-healing. Drawing on Freud's and Winnicott's work on psychoanalysis and play, R.M. Simon illustrates the healing power of art-making with the drawings and stories of seven-year-old Joe, who succeeds in overcoming the trauma of family break-up by expressing his emotional turmoil outside the formal therapeutic process. The progress from symbolising unconscious distress to verbalising and becoming conscious of (and able to deal wi.